Tacrolimus-associated sinusoidal obstruction syndrome after living-related liver transplantation - Kotenko, O. H.; Matviienkiv, A. O.; Hryhorian, M. S.; Minich, A. A.; Kotenko, I. O.; Mykhailiuk, O. S. (Zaporozhye Medical Journal, 2023)
Sinusoidal obstruction syndrome (SOS), previously known as hepatic veno-occlusive disease, is manifested by obliterating inflammation of the terminal hepatic veins, characterized by hepatomegaly, right upper quadrant pain, jaundice and ascites, and most often occurs in patients after hematopoietic stem cell transplantation and usually in those who received platinum-based drugs. Cases of SOS development in patients after transplantation of solid organs (lungs, pancreas, liver) are also reported in the world literature. These incidents are rare, and isolated and poorly studied after living-related liver lobe transplantation. The diagnosis is based on clinical signs, imaging techniques (according to ultrasound and radiological methods of examination), histological assessment of liver biopsy. Tacrolimus has been reported to be a causative agent that potentially plays a role in the pathophysiological mechanism of SOS. Aim. To study the relationship between the use of prolonged-release tacrolimus and the development of SOS in patients after living-related liver transplantation. Clinical case. In this article, we present a case of SOS after living-related liver transplantation which was associated with a toxic effect of prolonged-release tacrolimus (“Envarsus”). In a 55-year-old man, after living-related liver transplantation, high blood concentrations of tacrolimus associated with uncontrolled drug intake were detected. When performing a number of laboratory and instrumental methods of examination due to a massive ascites manifestation, the diagnosis of SOS was made. The study was carried out in accordance with the principles of the Helsinki Declaration. The informed consent was obtained from the patient for conducting the studies. Conclusions. By ruling out other possible contributing factors, including an acute rejection crisis, it was concluded that prolonged-release tacrolimus (“Envarsus”) was the cause of SOS.